A new Eurasian Bloc? Characterizing the activity of former Soviet and Turkic countries at the UN General Assembly - Monteiro, Vlademir; Santana, Vinícius; Mesquita, Rafael (Estudios Internacionales, 2023)
Soviet countries were the most cohesive bloc in the UN General Assembly (UNGA) during the bipolar era, after which the East-West cleavage was replaced by a North-South division. Hence, the Soviet space fell out of the attention of UN research in the post-Cold War era. However, this North-South polarization arises mainly from voting analyses that ignore other interstate activities at the UN. An analysis of sponsorship patterns of draft resolutions from the last decade, in contrast, reveals alternative groups, including a cluster with former Soviet, Eastern European, and Turkish-speaking countries, suggesting some unity among Armenia, Azerbaijan, Belarus, Kazakhstan, Kyrgyzstan, Russia, Tajikistan, Türkiye, Turkmenistan, and Uzbekistan. In light of such evidence, this exploratory paper uses data on UNGA sponsorship between 2009 and 2019 to descriptively characterize this newfound coalition of Eurasian countries, probing what their pattern of UNGA activity is and what topics bind them together as a group.